Hydro-climatic variability in southern Ecuador reflected by tree-ring oxygen isotopes - Volland, Franziska; Pucha, Darwin; Bräuning, Achim (ERDKUNDE, 2016)
Variations of stable oxygen isotopes in tree-ring cellulose are a widely used proxy to reconstruct hydro-climate variability in tropical and subtropical regions. We present the first δ18O chronology from annual tree rings in tropical Cedrela montana trees growing in the mountain rain forest of the Podocarpus National Park (PNP) in southern Ecuador. The more than a century long data record (1885–2011) comes from up to 15 individual trees (1980–2005) and represents the best-replicated isotope tree-ring chronology from the tropics. In comparison with tree-ring width, stable isotope variations show considerably higher correlations between individuals and thus represent a more reliable climate proxy in this very humid environment. High teleconnections to other stable isotope chronologies from the Amazon lowland indicate a high degree of consistency of regional hydro-climate variations. The PNP δ18O record is correlated with seasonal precipitation (January to April, CRU TS 3.21), frequency of wet days, and cloud cover over the Andean Cordillera Real. Spatial correlations indicate that the El Niño-Southern Oscillation (ENSO) has strong impact on tree-ring δ18O variations. Sea Surface Temperatures (SSTs) of the Niño 3.4 region and Niño 4 region, and the Oceanic Niño Index (ONI) show strong positive correlations with Cedrela oxygen isotope ratios, whereas the ENSO precipitation index correlates negatively. The Niño 3.4 and 4 SST influence is stronger after 1960 than before, indicating a shift in the influence of the Pacific Ocean on moisture variations in the Ecuadorian Andes. In the same period, the positive correlation with oxygen isotope signals from Andean glacier ice cores (r=0.2; p<0.05, 1894–1993) increased strongly (r=0.51; p<0.01, 1960–1993). In conclusion, stable oxygen isotope series from tropical tree species can help reconstruct variations in the hydroclimate of the Andean mountains and their surrounding areas.